METHODOLOGICAL APPROACHES TO THE GEOGRAPHICAL ANALYSIS OF URBAN DEVELOPMENT–RELATED PROBLEMS - Nargiza Rasulova (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This scientific article examines the methodological foundations for studying territorial, socio-economic, and environmental problems arising in the process of urban development from a geographical perspective. The scientific potential and practical effectiveness of traditional and innovative research approaches used in urban geography are analyzed. In particular, the role of geographic information systems (GIS), remote sensing, statistical, and comparative-geographical methods in assessing the development characteristics of urban areas is substantiated. The research findings serve as a scientific and methodological basis for developing strategic decisions aimed at ensuring sustainable urban development.